Implementing shared decision-making on acute psychiatric wards: a cluster-randomized trial with inpatients suffering from schizophrenia (SDM-PLUS). (2020) - Hamann, J.; Holzhüter, F.; Blakaj, S.; Becher, S.; Haller, B.; Landgrebe, M.; Schmauß, M.; Heres, S.
Abstract: Aims: Although shared decision-making (SDM) has the potential to improve health outcomes, psychiatrists often exclude patients with more severe mental illnesses or more acute conditions from participation in treatment decisions. This study examines whether SDM is facilitated by an approach which is specifically adapted to the needs of acutely ill patients (SDM-PLUS). Methods: The study is a multi-centre, cluster-randomised, non-blinded, controlled trial of SDM-PLUS in 12 acute psychiatric wards of five psychiatric hospitals addressing inpatients with schizophrenia or schizoaffective disorder. All patients fulfilling the inclusion criteria were consecutively recruited for the trial at the time of their admission to the ward. Treatment teams of intervention wards were trained in the SDM-PLUS approach through participation in two half-day workshops. Patients on intervention wards received group training in SDM. Staff (and patients) of the control wards acted under 'treatment as usual' conditions. The primary outcome parameter was the patients' perceived involvement in decision-making at 3 weeks after study enrolment, analysed using a random-effects linear regression model. Results: In total, 161 participants each were recruited in the intervention and control group. SDM-PLUS led to higher perceived involvement in decision-making (primary outcome, analysed patients n = 257, mean group difference 16.5, 95% CI 9.0–24.0, p = 0.002, adjusted for baseline differences: β 17.3, 95% CI 10.8–23.6, p = 0.0004). In addition, intervention group patients exhibited better therapeutic alliance, treatment satisfaction and self-rated medication compliance during inpatient stay. There were, however, no significant improvements in adherence and rehospitalisation rates in the 6- and 12-month follow-up. Conclusions: Despite limitations in patient recruitment, the SDM-PLUS trial has shown that the adoption of behavioural approaches (e.g. motivational interviewing) for SDM may yield a successful application to mental health. The authors recommend strategies to ensure effects are not lost at the interface between in- and outpatient treatment. Trial registration: The trial was registered at Deutsches Register Klinischer Studien (DRKS00010880).